Physical Function, Relocation, and Mortality Outcomes in Residential Care and Assisted Living Residents. (July 2019) - Phillips, Lorraine J.; Leary, Emily; Blankenship, Jody; Zimmerman, Sheryl
Objective: This study aimed to identify predictors of 6-month physical function and 12-month relocation or death in 272 residents of 34 residential care/assisted communities.Method: Measures collected at baseline, 6, and 12 months included health and demographic characteristics; self-reported pain, fatigue, and depressive symptoms; exercise self-efficacy, barriers, and expectations; attitudes on aging; performance-based physical function and physical activity; and community demographics, programs, and policies. GLIMMIX procedures for regression analyses with community as a random effect were run.Results: Better baseline physical function and grip strength, female sex, and residential care community predicted better 6-month physical function. At 12 months, 25.6% had relocated or died. The odds of 12-month relocation or death for 1-point increase in physical function score was 0.84 and for 1-point increase in depression score was 1.16.Discussion: Targets to promote longer tenure in residential care/assisted living include programs to ameliorate functional decline and depression screening and treatment.